Performance of pultruded GFRP composites under tropical climate - Mohamad Yatim, Jamaludin (2003)
Glass fibre reinforced polymer (GFRP) is a composite material, which consists of polyester thermosetting resin as matrix and glass fibres as reinforcement. GFRP is mainly used as structural sections and as structural rehabilitation and repair material. It is observed that the current required technical and design data of pultruded GFRP sections is rather limited especially with regard to material properties and its performance in the tropical climate. Therefore, this study is conducted experimentally to investigate the engineering properties ofthe GFRP material and sections, and its performance to the local tropical climate. Special observations on the effects of the fibre orientations and stacking sequences in laminates are also made. Testing procedures are basically in accordance with the requirements of the American Standard of Testing and Materials (ASTM), and the British Standards (BS). There are six different fibre orientations ofGFRP plates and two different fibre orientations ofGFRP box sections of6.35 mm nominal thickness with different stacking sequence selected for the test samples. They were fabricated by local manufacturer according to the commercial quality requirements. A total of 2304 GFRP samples were tested, 1152 of the samples were exposed to the outdoor environment, while the other 1152 samples were kept in the laboratory environment as control samples. The samples were tested for physical and mechanical performance. Among the visual observations made were the surface appearance, thickness variation and weight gain. Samples were also tested for tension, compression and in-plane shear to indicate the mechanical performance. Measurements were taken at 3, 6, 12 and 24 months period of exposure to weathering. Four point bending tests were also conducted on 900 mm span of GFRP box section beams to investigate the structural performance under tropical weather. Twenty-four beams were tested for this purpose after being exposed to the outdoor environment and the other twenty-four beams were tested under controlled environment. The statistical test data were analysed using Weibull distribution. The test results showed that the GFRP material is significantly affected by tropical weather conditions. In general, surface degradation was significant after 12 months exposure due to fungal attack. Surface roughness and discoloration on the top surface of the samples were also observed with the bottom surface not affected by the exposure at all. The effect of tropical weather conditions on mechanical performance ofthe exposed GFRP samples was significant, but varied with fibre quantity. The reduction in flexural capacity ofGFRP box beams was also observed due to weathering after a period of24 months. Ultimately, the mechanical properties and structural beam performance with respect to the period of exposure under tropical weather was formulated and presented at the end ofthis study.